Engineering considerations for the coating area of a service company - Shapoval, V. (Запоріжжя: ТДАТУ, 2026)
Designing a painting (coating) section begins with developing the key engineering and organizational solutions for performing painting operations in accordance with the technological workflow of machine repair. The process requires strict compliance with environmental, fire-safety, and sanitary regulations (a separate building or full isolation, high-capacity supply-and-exhaust ventilation). The essential components include a paint-and-drying booth, surface preparation zones, paint mixing and matching areas, proper lighting, and the use of explosion-proof equipment.
Keywords: repaired products; machine repair